ChemInform Abstract: A Review on Natural Surfactants. Issue 39 (September 2015) - De, Sourav; Malik, Susanta; Ghosh, Aniruddha; Saha, Rumpa; Saha, Bidyut
Abstract Review: properties, advantages and drawbacks, production, characterization and applications; 84 refs.